Dancing Faith, Reproducing Identity: The Lord of Miracles Devotion Among Barcelona’s Migrants - Wilson Muñoz-Henríquez; María Esther Fernández-Mostaza (Religions, 2025)
The procession of El Señor de los Milagros is a multitudinous religious manifestation originally from Peru that tours numerous cities around the world each year in October. In Barcelona (Spain), the procession centers the diverse dances performed in honor of the “Cristo Moreno”, especially La Marinera, which is considered the cultural heritage of the Peruvian nation and is performed mainly by dance groups formed by new generations of Peruvian migrants’ children. This article analyzes the relationship between new generations and the practice of dancing La Marinera in honor of El Señor de los Milagros in Barcelona. Our main methodological strategy was an ethnography focused on the processions held in Barcelona (Spain) in 2016, 2017, 2018, and 2022. We also conducted in-depth interviews with key informants and focus groups and a review of documents and historical information. In this article, we will show that the performance of the Marinera dance in the procession can foster a connection between young dancers and the worship of the Lord of Miracles. Its performance promotes the appreciation and safeguarding of this practice as a distinctive cultural and national element of Peru, also allowing for a public staging oriented toward spectacle, framed in a transnational and globalized context.